Arachne-A web-based event viewer for MINERνA - Tagg, N.; Brangham, J.; Chvojka, J.; Clairemont, M.; Day, M.; Eberly, B.; Félix, J.; Fields, L.; Gago, A.M.; Gran, R.; Harris, D.A.; Kordosky, M.; et al. (Elsevier, 2012)
Neutrino interaction events in the MINERVA detector are visually represented with a web-based tool called Arachne. Data are retrieved from a central server via AJAX, and client-side JavaScript draws images into the user's browser window using the draft HTML 5 standard. These technologies allow neutrino interactions to be viewed by anyone with a web browser, allowing for easy hand-scanning of particle interactions. Arachne has been used in MINERVA to evaluate neutrino data in a prototype detector, to tune reconstruction algorithms, and for public outreach and education.
Keywords: Particle physics outreach; https://purl.org/pe-repo/ocde/ford#1.03.03